Cadmium Application in Tomato: Nutritional Imbalance and Oxidative Stress - Nogueirol, Roberta Corrêa; Monteiro, Francisco Antonio; Gratão, Priscila Lupino [UNESP]; de Alcântara da Silva, Berenice Kussumoto; Azevedo, Ricardo Antunes (Springer Nature, 2016)
Over the last few decades, the concentration of cadmium (Cd) in the environment has increased considerably in many countries due to anthropogenic activities. Cd is one of the most toxic pollutants in the environment and affects many metabolic processes in plants. The main objective of this study was to evaluate the response of the production, nutritional, and enzymatic antioxidant system of two tomato genotypes (Calabash Rouge and CNPH 0082) grown in tropical soils that were treated with doses of Cd. Soil samples were collected from the layer of earth at a depth of 0–0.2 m in areas subjected to a minimum of human disturbance. The concentrations of Cd applied to the soil samples were 0, 1, 2, and 4 times (0, 3, 6, and 12 mg kg−1 of Cd) the agricultural intervention value adopted by current environmental legislation in the state of São Paulo, Brazil. Analysis of superoxide dismutase, catalase, glutathione reductase, guaiacol peroxidase, and ascorbate peroxidase activities, formation of stress indicator compound (malondialdehyde—MDA and hydrogen peroxide), parameters of production—dry mass of the shoot and root system (here in after “shoots” and “roots”), as well as nutrition, and both the bioavailable and total levels of this metal in the soil were performed. When the bioavailable content and total levels of Cd in the soil increased as a result of this metal doses applied, the biomass of both shoots and roots decreased in both genotypes (with the exception of the CNPH 0082 grown in clay soil) and displayed lower SPAD (relative chlorophyll index) values when exposed to contaminated environments with Cd concentrations. Cadmium treatment resulted in nutritional imbalances, mainly in terms of N, P, and Mn metabolism. Plants subjected to an elevated available content of metal in the soil exhibited increases in content of MDA and hydrogen peroxide and increased activity of catalase, ascorbate peroxidase, and guaiacol peroxidase in plant tissues when grown in both clay soil and sandy soil. Cadmium was phytotoxic to the plants causing a nutritional imbalance, especially on the metabolisms of N, P, and Mn. An oxidative stress condition was established in response to the Cd treatments applied, which led to changes in peroxidase activity.
Keywords: Antioxidant enzymes; Extractants; Mineral plant nutrition; Toxic element; Tropical soils